Adding a protective screw improves hinge's axial and torsional stability in High Tibial Osteotomy. (April 2020) - Jacquet, Christophe; Marret, Auriane; Myon, Robin; Ehlinger, Matthieu; Bahlouli, Nadia; Wilson, Adrian; Kley, Kristian; Rossi, Jean-Marie; Parratte, Sebastien; Ollivier, Matthieu
Abstract: Backgrounds: Despite the use of a locking plate a 30% incidence of lateral hinge fracture after Open-Wedge High Tibial Ostetomy was described in the literature. A finite element model was used to analyze if the presence of a hinge-securing screw in the osteotomy area, using Patient Specific Cutting Guides with a locking plate, decreases the stresses within the lateral hinge during compression and torsion. Methods: A 3D model of a tibial sawbone was used to simulate an opening wedge of 10°. To apply loads on the tibial plateau, two supports were modelled on each tibial plateau to simulate the femoral condyles forces. A two second model with a hinge-stabilizing was defined with two different screws (diameter 2 mm and 4 mm). Two cases of static charges were considered 1) compression test (2500 N) 2) Torsion test (along the tibial mechanical axis). Findings: During compression simulation, 17% of the total surface of lateral hinge was stressed between 41-50Mpa without hinge-securing screw while the amount of surface under stress between 41 and 50 MPa dropped significantly under screw stabilization (1% for the 2 mm and 3% for the 4 mm). During torsion stress simulation a decrease of the value of the maximal stress in the lateral hinge was also observed with the addition of a hinge-securing screw (37 MPa without screw, 27Mpa with a 2 mm screw and 25 Mpa with a 4 mm screw). Interpretation: Positioning a screw intersecting the cutting plane at the theoretical lateral hinge location associated with a locking plate reduces lateral hinge stress in both compression and torsion. Those findings need to be confirmed by further specimens' mechanical testing. Highlights: A 3D model of a left tibial was used to simulate a high tibial osteotomy with an opening wedge of 10°. Analogously a second model with a hinge-stabilizing screw inserted at the hinge point was created. The two models were tested using finite element analysis in both Compression and Torsion Settings. The screw stabilized model exhibited reduced lateral hinge stress in both compression and torsion. A 4 mm screw was superior to a 2 mm in terms of hinge stabilization.